The effect of project-based learning model assisted by interactive digital modules on scientific literacy in biotechnology topic in in 9th grade of junior high school - Nabilla Vidia Sobach; Rini Rita T. Marpaung; Dina Maulina; Berti Yolida (Assimilation: Indonesian Journal of Biology Education, 2023)
Low scientific literacy skills, teaching materials used in learning are not facilitated by students to understand science concepts and apply them in everyday life. The purpose of this study was to determine the effect of project-based learning models that help digital interactive modules on students' scientific literacy skills and students' responses to digital modules on the subject matter of biotechnology. The population in this study was 9th grade of junior high school at Bandar Lampung with sampling techniques, namely purposive sampling techniques, class IX-9 as an experimental class and class IX-8 as a control class. The results showed that there was a significant influence on the use of a project-based learning model of digital interactive module assistance on scientific literacy skills between control classes and experiments on biotechnology subject matter in 9th grade Junior High School with a significance value of independent sample t test of 0.001. The results of student responses to the digital interactive module obtained an average proportion of 89% in the excellent category.